The Newest Vital Sign: Frequently Asked Questions - Barry D. Weiss (SLACK Incorporated, 2018)
The Newest Vital Sign (NVS) is one of the most widely used health literacy screening instruments (Shealy & Threatt, 2016; Weiss et al., 2005). The original version of the NVS was developed in English and Spanish and validated in the United States for identifying people with limited health literacy skills (Weiss et al., 2005). Since then, the NVS has been adapted and validated for use in other languages and countries, including the United Kingdom (Rowlands et al., 2013), the Netherlands (Fransen et al., 2014), Japan (Kogure et al., 2014), Italy (Capecchi, Guazzini, Lorini, Santomauro, & Bonaccorsi, 2015), Kuwait (Al-Abdulrazzaqa, Al-Haddadb, AbdulRasoula, Al-Basarib, & Al-Taiara, 2015), Brazil (Rodrigues, de Andrade, González, Birolim & Mesas, 2017), China (Xue et al., 2018), and Canada (Mansfield, Wahba, Gillis, & Weiss, 2018). It has also been adapted for administration in American Sign Language (McKee et al., 2015).